Metascience - Wray, Brad.; Simon, Jonathan; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Metascience is a review journal which publishes high quality, comprehensive reviews of books in the fields of history and philosophy of science and science and technology studies. Metascience specialises in innovative styles of reviewing, including book symposia, essay reviews, survey reviews and standard reviews. It is the aim of Metascience to have the widest possible coverage. Thus, books which are not reviewed are presented in short descriptive notices. Metascience is non-specialist in that reviews are accessible to a wide cross-section of the science studies community.
Keywords: History; Philosophy and science; Biology -- Philosophy; Philosophy; Philosophy of Science; History, general; Philosophy of Biology; Philosophy of Technology